ANALISIS PENGARUH WORK ENGAGEMENT DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi Pada Kantor Pusat PDAM Tirta Moedal Kota Semarang) - Kustya, Novela Destha; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2020)
This study aims to determine the effect of work engagement and leadership on employee performance through organizational commitment as a intervening variable on the Head Office of PDAM Tirta Moedal, Semarang City. This study uses data through the distribution of research questionnaries, and secondary data through journals and books.This study uses a probability sampling technique that is a random sampling. The sample in this study were employees at the Head Office of PDAM Tirta Moedal, Semarang City, whose dound 75 people. The data analysis technique used in this study is Partian Least Square with SmartPLS 3.2.9 application to find path coefficients, and the direct or indirect influence of exogeneous on endogeneous variables.Â Analysis of the statistical testing result use alpha Î± = 0,05. While the results of the study show that work engagement has a significant positive effect on employee performance and organizational commitment, leadership has a significant positive effect on employee performance and organizational commitment, and organizational commitment had a positive and significant effect on employee performance. In addiction, organizational commitment variables can mediate an indirect relationship between leadership on employee performance but not to work engagement on employee performance